2011
DOI: 10.4028/www.scientific.net/amm.71-78.2787
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Grouting Treatment and Flow Numerical Simulation for the Landslide Area of Dalian Metro

Abstract: The study discusses the simulation analysis based on the modflow software. Generalize body site, zone and boundary conditions of simulation, make a finite element model based on the geology of the Collapse of Lot 110 , Dalian Metro. Determine the accuracy of the simulation results based on the comparison between the test and the field measurement data. And then predict the flow of groundwater and the penetration. Base on the software simulation of the surface displacement and field observation wells pumping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Geothermal resource [1][2][3][4] is a very clean energy, whose exploration and development has a history of nearly a century, especially in Iceland, Italy, New Zealand, etc. But on a global scale, it has been used as a kind of new energy to carry on the exploration and development only in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal resource [1][2][3][4] is a very clean energy, whose exploration and development has a history of nearly a century, especially in Iceland, Italy, New Zealand, etc. But on a global scale, it has been used as a kind of new energy to carry on the exploration and development only in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…When loading bulk cargo in the tween deck [4], the hatch cover should be closed if the loading data is clearly shown that opening hatch cover will result the overloading of the ship' bottom. The goods should be properly trimmed.…”
Section: Advances In Engineering Research Volume 150mentioning
confidence: 99%